Evaluasi Kurikulum Pendidikan: Memastikan Proses Pembelajaran Sesuai dengan Tujuan Pendidikan - Ibrahim, Ibrahim; Zainuri, Ahmad; Yunita, Yunita; Kanada, Rabial; Hidayat, Hidayat (El-Idare, 2023)
This article discusses the evaluation of the educational curriculum at the Aulia Cendikia Islamic Boarding School in Palembang, with the background that curriculum evaluation is an important activity in the implementation of education in an educational institution. This type of research is qualitative, with a descriptive approach. The method used in collecting data is through interviews, observation, and documentation. To analyze the data starting from data collection, data reduction, data presentation, and data verification. Results obtained, namely the implementation of the evaluation of the Education Curriculum at the Aulia Cendikia Islamic Boarding School in Palembang has been carried out in accordance with the procedures for implementing the evaluation of the educational curriculum. Curriculum evaluation plays an important role both in determining educational policy in general, as well as in making decisions in the curriculum. The results of curriculum evaluation can be used by educational policy holders and curriculum holders in selecting and determining policies for developing the education system and developing the curriculum model used. The results of curriculum evaluation can also be used by teachers, school principals and other education implementers, in understanding and assisting student development, selecting learning materials, choosing methods and learning aids, methods of assessment and other educational facilities.